Clinical predictors of steroid resistance in childhood nephrotic syndrome - ÇİÇEK DENİZ, NESLİHAN (My University, 2023)
We aimed to evaluate the clinical parameters, histopathological findings of nephrotic syndrome (NS) patients, and independent factors predicting steroid resistance in a single tertiary center. One hundred and sixty-two children (57 girls and 105 boys) with NS who were followed between 1998 and 2018 were analyzed in this retrospective cohort. The median (interquartile range; range) age and follow-up time were 4.9 (5.7; 0.1-16.8) and 5.5 (5.4; 0.1-20.3) years. A total of 82.7% of the patients were steroid-sensitive nephrotic syndrome (SSNS) and 17.3% were steroid-resistant nephrotic syndrome (SRNS). The median age at first presentation was lower in the SSNS group (P = .002). The most common histopathological findings were focal segmental glomerulosclerosis (FSGS) and minimal change disease (MCD). Hypertension and macroscopic and microscopic hematuria were higher in the SRNS group (P < .001). The age and microscopic hematuria were independent risk factors for steroid resistance (P = .019 and P = .002, respectively). Complement 3 (C3) was evaluated in 148 patients and found low in 7 patients who were subsequently diagnosed as membranoproliferative glomerulonephritis. There is still no better clinical predictor for steroid response than late age of onset and microscopic hematuria. Hypertension may also give a hint for potential steroid resistance.